Spot simulation for urban study - Dulbahri Dulbahri (Faculty of Geography, Universitas Gadjah Mada, 1986)
This paper discusses the SPOT simulation performances with Toulouse area as an example. An Overflight of the Toulouse area was made; resampling of 10 m and 20 m resolution combining with XS/ and XS2 in the creation of the simulation image was used in an effort to study Toulouse urban area. Manual interpretation without fieldchecks is used in this study. Toulouse urban land use can be distringuished and is easily delineated. Based on spectral characteristics, roof reflectance, road pattern, texture, and shape analysis the relative urbanization can be known. The relative network density can be measured so that the building and population density can be estimated using the SPOT simulation image.